Some design problems of thin shell structures - Johns, D. J. (College of Aeronautics, 1961)
Simplified analyses are presented which illustrate some of the design problems of typical space vehicle structures, with the emphasis on thin, circular cylindrical shells. Amongst the problems considered are panel flutter, thermal buckling and buckling under axial compression.